Fracture resistance of root-filled teeth after cavity preparation with conventional burs, Er: YAG and Er,Cr: YSGG lasers - Uğur Aydın; Fatih Aksoy; Samet Tosun (Istanbul University, 2018)
Purpose The aim of the present study is to compare the fracture resistance of teeth after access cavity preparation with conventional rotary burs, Erbium-doped yttrium aluminum garnet laser (Er:YAG) and Erbium, cromium: yttrium scandium gallium garnet laser (Er,Cr:YSGG) lasers. Materials and methods Fifty five intact mandibular molars were divided into 3 negative groups (groups 1, 2, 3; n=5 for each), 3 study groups (groups 4, 5, 6; n=10 for each) and 1 positive control group (intact teeth; n=10). Access cavities of groups 1, 2 and 3 were prepared with conventional burs, Er:YAG laser and Er,Cr:YSGG laser respectively. After root canal obturation, their coronal portions were left non-restored. Access cavities of groups 4, 5 and 6 were prepared by using the same equipment but their coronal portions were restored with composite resinafter root canal obturation. Following thermocycling, fracture strength was evaluated with a Universal Testing Machine. Mean force at which each sample is fractured was recorded in Newton unit and statistically analyzed. Results Fracture resistance of group 7 (intact teeth) was significantly higher than all other groups (p<0.001). Differences among the fracture resistance values of groups 4, 5 and 6 were not significantly different but they were significantly higher than those of groups 1, 2 and 3 (p<0.001). No significant difference was found between Groups 1, 2 and 3. Conclusion Preparing access cavities with either laser or bur has no effect on the fracture resistance of teeth with root canal treatment.